Election Decision Support System Election Management Devices (Elections) Kaur District - Ujang Juhardi; Diana Diana; Deddy Abdullah; Andri Saputra (Jurnal Komputer, Informasi dan Teknologi, 2022)
Law number 15 of 2011 concerning General Election Organizers states that the election organizer is an institution that organizes elections consisting of the General Election Commission and the Election Supervisory Body as one unit. Elections that are stored in Regency/City are called Regency/City KPUs as described in Law No. 15 of 2011. In sending the KPU, the KPU is assisted by the Election Committee (PPK), Voting Committee (PPS), and Voting Organizers (KPPS). ) as described in Article 3 of the General Election Commission Regulation Number 3 of 2018. These PPK, PPS, and KPPS were established directly by the Regency/City KPU as stated in Article 10 paragraphs 1 to 3 of Law No. 15 of 2011. Currently the formation and the selection process for some of these institutions is still manual. Currently there is an instrument that will assist in supporting decisions based on mathematical calculations called the Decision Support System (DSS). DSS is a system that functions to provide information, predict, and direct options to information users in order to make decisions.